The impact of the migration processes on the low cost airlines' routs between EU countries and Poland after its accession to the EU, and on the territorial cohesion of Polish regions. - Lukasz Olipra; Ewa Pancer-Cybulska; Ewa Szostak (European Regional Science Association (ERSA), 2011)
After the accession of Poland to the European Union in 2004 we could observe two phenomena: huge emigration of Poles to the old member states of the EU (mainly to United Kingdom and Ireland) and on the second hand a very dynamic increase in the number of flight destinations from regional airports served by low cost carriers (what meant also increase in the number of passengers). The aim of this article is to answer the question, whether directions of the emigration after accession of Poland to the European Union had a significant impact on the routes of low cost airlines in Poland. Whether we can say, that the migration forced LCCs to establish new flights and connections in a particular direction or not? And if yes - to what extent. What is happening when emigrants are coming back to Poland. If there are significant relation between movement of migrants and number of flights of low cost carriers from Polish airports? Finally, can we say, that growing emigration and growing number of LCCs flights helped to improve territorial cohesion of Polish regions with the core of Europe? What is the scale of this improvement and what is the mechanism of this? What kind of policy can regional authorities introduce in this area to strengthen territorial cohesion of Polish regions with the rest of Europe? To answer all these questions authors want to compare and analyze statistics of migration and original data concerning number and destination of LCCs flights from Polish regional airports. To answer questions stated above statistical methods will be used.
Keywords: 330